Prevalensi Dan Identifikasi Vektor Potensial ASF (African Swine Fever) di Kota Kupang - Almet, Julianty; Wuri, Diana A; Djungu, Dewi F.L (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
African Swine Fever (ASF) is a deadly viral disease of pigs that poses a serious threat to livestock farming in Kupang Regency. This study aimed to identify potential vectors of ASF, particularly ticks, and determine their prevalence in the region. The research was conducted from April to July 2023 in three sub-districts: West Kupang, East Kupang and Takarai, using manual sample collection and laboratory identification techniques. Ticks were collected directly from pigs using tweezers, preserved in 70% alcohol, and processed at the Helminthology and Entomology Laboratory. Identification was done through clearing with 10% KOH, multistage dehydration, and microscopic observation with 40x magnification. Data were analysed descriptively to determine the type and prevalence of potential ASF ticks. The results showed that three types of potential ticks were identified: Ixodes sp., Boophilus sp. and Ornithodorus sp. The prevalence of each ticks species and their potential transmission of ASF virus were comprehensively evaluated. This study makes an important contribution to understanding the dynamics of ASF transmission through ticks vectors in the Kupang region.